Hoogsteen Base Pairings - Neelabh Datta (Journal of Experimental and Molecular Biology, 2022)
In contrast to Watson-Crick (WC) base pairing, Hoogsteen (HG) base pairing involves flipping a purine base 180° between its anti and syn conformation. Recent studies have shown that HG pairs coexist in dynamical equilibrium, and several biological functions depend on them. This significance has stirred computational research on this base-pairing transition. However, a methodical reproduction of sequence variations has continued to be out of reach. It is becoming increasingly clear that Hoogsteen base pairs play a crucial role in DNA replication, recognition, damage repair, and incorrect sequence repair. The Protein Data Bank contains a variety of Hoogsteen base pairing modes that include the preference for A–T versus G–C bps, TA versus GG steps, and a preference for 5'-purines at terminal ends. RNA A-form duplexes are strongly disfavored by Hoogsteen base pairs, in stark contrast to B-form DNA. Therefore, N1-methyl adenosine and N1-methyl guanosine, which transpire in DNA as alkylation impairment and in RNA as posttranscriptional adjustments, have great differences in effects. They create G–C+ and A–U Hoogsteen base pairs in duplex DNA that preserve the structural integrity of the double helix, but obstruct base pairing altogether and induce local duplex melting in RNA, providing a mechanism for potently disrupting RNA structure through posttranscriptional modifications. In duplex DNA, they maintain the structural integrity of the double helix by creating G–C+ and A–U Hoogsteen base pairs, but block base pairing altogether and cause local duplex melting in RNA, thus providing a potent means for disrupting RNA structure post transcriptionally. As a result of the markedly different inclinations for B-DNA and A-RNA to form Hoogsteen base pairs, they may be able to balance the opposing demands of maintaining genome stability and dynamically modulating the epitranscriptome. This review examines the occurrence of Hoogsteen base pairs in DNA and RNA duplexes.